Digital Storytelling for Social Inclusion: A Qualitative Study with Marginalized Youth - Dini Anggraheni; Ahmet Demir; Baran Akbulut (Yayasan Adra Karima Hubbi, 2025)
Digital storytelling has emerged as a powerful pedagogical and social tool, enabling marginalized youth to articulate their experiences, build digital literacy, and foster a sense of belonging in increasingly mediated societies. Social exclusion continues to affect vulnerable groups by limiting their opportunities for participation and self-expression, which in turn impacts personal identity and community integration. This study aims to explore how digital storytelling can be employed as an inclusive practice to promote voice, agency, and connection among marginalized youth. A qualitative research design was adopted, using a multiple case study approach with 45 participants from diverse disadvantaged backgrounds, including urban slum communities and rural low-income settings. Data were collected through participatory workshops, semi-structured interviews, and observation, and analyzed thematically. Findings reveal that the process of creating and sharing digital stories enables participants to express personal narratives, develop confidence, enhance collaborative skills, and foster empathy within their peer networks. The study concludes that digital storytelling, when designed as a participatory and reflective practice, can contribute significantly to social inclusion by strengthening the visibility, resilience, and sense of belonging of marginalized youth. The study highlights the need for educators and community organizations to integrate digital storytelling into inclusive educational and community development strategies.